UPAYA MENJAGA HADIS DARI PEMALSUAN: PERSPEKTIF ABI AL-HASAN IBN ‘ALI IBN MUHAMMAD IBN ‘IRĀQ AL-KINĀNĪ - Rani Zaindina; Muhid; Isnaini Lu’lu’ Atim Muthoharoh (Al-Majaalis : Jurnal Dirasat Islamiyah, 2025)
This research starts from the incident of hadith falsification which became a color in the history of the development of Islam. Because the forgery of fake hadiths is growing and endangering the understanding of the Islamic religion, the ulama are making several efforts to protect hadiths, namely; researching the characteristics of the narrator and his narration, giving warnings to liars, testing the truth of a hadith by comparing the history of other channels whose authenticity has been acknowledged, establishing general rules for knowing the characteristics of the hadith of Maud}u' and memorizing the hadith and its quality, giving birth to a work that specifically discusses fake hadith. This research uses a qualitative descriptive approach, the author presents data related to the efforts of ulama in preserving hadith. One of them is Ibn 'Irāq al-Kinani who is one of the scholars who protects the hadith through his work. The findings in this research indicate that Ibn 'Irāq al-Kināni's efforts are involved in overcoming the problem of fake hadith, his efforts stated in his book Tanzīh al-Sharī'ah al-Marfū'ah 'An al-Akhbār al-Shanī'ah al-Maudū'ah. There are several efforts contained in this book, including; mentioning the names of people accused of lying and falsifying hadiths, mentioning the groups that falsified hadiths, and mentioning false hadiths which then Ibn 'Irāq al-Kināni explained the causes of corruption in the hadiths so that they became false hadiths.